Design considerations for two-flight reinforced concrete stairs - Liao, Changmin (Kansas State University, 2020)
The reinforced concrete stairs are commonly used in the built environment for many years. In the early 20th century, the use of steel as the structural system for stairs has increased, and reinforced concrete has decreased as the most common structural material. However, the ability to make any shape, readily available materials, the compressive strength, and outstanding fire resistance of reinforced concrete ensure that it is a vital material in the built environment. Especially for stairs serving as egress for people to evacuate under severe conditions, reinforced concrete as a building material stands out. This report presents a design procedure for two-flight reinforced concrete stairs and provides a parametric study to analyze the relationship between flexural reinforcement and critical factors: reinforcement design methods, geographic locations, stair slab thicknesses, and boundary conditions. For this study, the materials are limited to normal weight concrete with ASTM 615 Grade 60 steel reinforcing with a specified yield strength of 60,000 psi. Twenty-four cases are designed with varying reinforcement design methods, geographic locations, stair slab thicknesses, and boundary conditions. The purpose of this report is to examine the differences in reinforcement design for reinforced concrete stairs.
Keywords: Reinforced concrete; Stair; Reinforced concrete stair; Two flight reinforced concrete stair